1974
DOI: 10.1136/oem.31.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of cadmium through bile and intestinal wall in rats

Abstract: of cadmium through bile and intestinal wall in rats. The excretion of Cd2+ through the bile and intestinal wall after intravenous administration of CdC12 in non-toxic doses (67, 90, and 120 ,ug of Cd2+ per rat) was studied in rats. The cumulative biliary excretion reached 24 hours after administration of the 67 jug dose was 0 83 %, after 90 jig 1-18 %, and after the 120 ,tg dose 5-68 % of the amount given. The highest excretion rate of Cd2+ was detected between 15 and 30 minutes after administration. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The relative excretion of cadmium in bile in percent of body burden of cadmium, as measured by whole body counting, was the same in both groups of rats, independent of the total administered cadmium dose. This finding is not in accordance with acute exposure studies, where higher dose levels have been shown to give a higher relative excretion (8,13,14) but does agree with the metabolic model of cadmium metabolism in humans proposed by Kjellstrom and Nordberg (26), and with empirical data from humans where cadmium levels in bile on group basis are related to liver concentrations of cadmium (23).…”
Section: Discussionsupporting
confidence: 31%
See 1 more Smart Citation
“…The relative excretion of cadmium in bile in percent of body burden of cadmium, as measured by whole body counting, was the same in both groups of rats, independent of the total administered cadmium dose. This finding is not in accordance with acute exposure studies, where higher dose levels have been shown to give a higher relative excretion (8,13,14) but does agree with the metabolic model of cadmium metabolism in humans proposed by Kjellstrom and Nordberg (26), and with empirical data from humans where cadmium levels in bile on group basis are related to liver concentrations of cadmium (23).…”
Section: Discussionsupporting
confidence: 31%
“…Biliary excretion of cadmium directly after a parenteral dose has been measured in rats by a number of authors (8,(12)(13)(14)(15)(16)(17)(18). Such studies have shown that initially the excretion of cadmium via bile is high.…”
Section: Introductionmentioning
confidence: 99%
“…Cikrt & Tichy (1974) have shown a dose-dependent excretion in the bile of between 0.8 and 5.7% of an intravenous pulse of cadmium. Finally cadmium is also excreted via skin, hair, sweat, nails and saliva but these routes are considered to be of only minor importance (CEC, 1978).…”
Section: Excretionmentioning
confidence: 98%
“…Within 24 hr after administration of Cd2+ to rats (67 fig Cd2+/rat, i.v. ), 0.83% of the dose is excreted in the bile and 5.31% in the entire gastrointestinal tract and feces (12). Approximately 10% of the administered dose (1 mg Cd2+/ kg, i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…administration of the cation to rats is the gastrointestinal tract (11)(12)(13). Within 24 hr after administration of Cd2+ to rats (67 fig Cd2+/rat, i.v.…”
Section: Discussionmentioning
confidence: 99%